Pervasive Risk Avoidance: Nursing Staff Perceptions of Risk in Person-Centered Care Delivery. (5th August 2020) - Behrens, Liza L; Boltz, Marie; Kolanowski, Ann; Sciegaj, Mark; Madrigal, Caroline; Abbott, Katherine; Van Haitsma, Kimberly
Abstract: Background and Objectives: Nursing home (NH) staff perceptions of risks to residents' health and safety are a major barrier to honoring resident preferences, the cornerstone of person-centered care (PCC) delivery. This study explored direct-care nursing staff perceptions of risk (possibilities for harm or loss) associated with honoring residents' preferences for everyday living and care activities. Research Design and Methods: Qualitative, descriptive design using sequential focus group (FG) methodology. Results: Participants ( N = 27) were mostly female (85%), had more than 3 years of experience (74%), and worked in NHs recently experiencing 6–12 health citations. Content analysis of 12 sequential FGs indicated nursing staff perceptions of risks may impede delivery of person-centered care. This is supported by the overarching theme: pervasive risk avoidance; and subthemes of: staff values, supports for risk-taking, and challenges to honoring preferences. Discussion and Implications: Development of a multidimensional framework with specific risk engagement measures that account for the unique risk perspectives of nursing staff will contribute significantly to the clinical management of older adult preferences and research on the effectiveness of preference-based PCC delivery in the NH setting.